2014
DOI: 10.4490/algae.2014.29.1.047
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial and synergistic effect of phlorotannins isolated from edible brown seaweed Eisenia bicyclis against acne-related bacteria

Abstract: To develop effective and safe acne vulgaris therapies with a continuing demand for new solutions, we investigated unique efficacy of an antibacterial agent from marine brown alga Eisenia bicyclis in treating acne vulgaris. The methanolic extract of E. bicyclis exhibited potential antibacterial activity against acne-related bacteria. The ethyl acetate fraction showed the strongest antibacterial activity against the bacteria among solvent fractions. Six compounds (1-6), previously isolated from the ethyl acetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 90 publications
(70 citation statements)
references
References 32 publications
4
63
1
2
Order By: Relevance
“…The median ∑FIC against L. monocytogenes strains ranged from 0.172 to 0.344. As described by Lee et al (2014), the synergistic ranges of FIC <1 were observed for all combinations of streptomycin and the EtOAc fraction against L. monocytogenes strains. Indeed, the median ∑FIC of the streptomycin-EtOAc fraction ranged from 0.172 to 0.344, suggesting marked synergy (Table 4).…”
Section: Antibiotic Resistance Of L Monocytogenes Strainsmentioning
confidence: 95%
See 3 more Smart Citations
“…The median ∑FIC against L. monocytogenes strains ranged from 0.172 to 0.344. As described by Lee et al (2014), the synergistic ranges of FIC <1 were observed for all combinations of streptomycin and the EtOAc fraction against L. monocytogenes strains. Indeed, the median ∑FIC of the streptomycin-EtOAc fraction ranged from 0.172 to 0.344, suggesting marked synergy (Table 4).…”
Section: Antibiotic Resistance Of L Monocytogenes Strainsmentioning
confidence: 95%
“…It has been demonstrated that one of the more effective strategies in developing new drugs or alternative therapies is the restoration of antibiotic activity, in combination with antibacterial materials derived from natural products and traditional medicines, against drug-resistant bacteria (Eom et al 2014;Lee et al, 2014). In this study, the interaction between the EtOAc fraction of E. cava and the commercial antibiotic streptomycin against L. monocytogenes strains was evaluated by FIC assay.…”
Section: Synergistic Effect Between Etoac Fraction Of E Cava and Strmentioning
confidence: 99%
See 2 more Smart Citations
“…, P. acnes , , 2 (Eom et al, 2016;Kim et al, 2016;Nam et al, 2003;Tan, 2003). , (Eom et al, 2016;Lee et al, 2014a , (Kim et al, 2009;Lee et al, 2014b;Poquet et al, 2008).…”
unclassified